Encyclopedia of RF and Microwave Engineering 2005
DOI: 10.1002/0471654507.eme155
|View full text |Cite
|
Sign up to set email alerts
|

Gyrators

Abstract: A gyrator is a nonreciprocal electrical network. It is capable of transforming signals or energy represented in terms of one electrical quantity, such as voltage or magnetic field, to another electrical quantity that may be of similar type or of a complementary type, such as current or electric field. Such networks are quite useful in electronic systems, since one often wishes to design systems with a limited set of component types or with restrictions regarding certain physical paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…One meta-analysis investigated the findings of 71 controlled studies and determined that a daily prednisolone dose < 10 mg or cumulative dose < 700 mg did not increase the risk of infectious complication. 24 Another study reported that a steroid dose ≥ 1 mg/kg per day over ≥ 21 days increased the risk of IPA. 25 Dexamethasone at 40 mg/day for 4-6 days is used as a steroid in some chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analysis investigated the findings of 71 controlled studies and determined that a daily prednisolone dose < 10 mg or cumulative dose < 700 mg did not increase the risk of infectious complication. 24 Another study reported that a steroid dose ≥ 1 mg/kg per day over ≥ 21 days increased the risk of IPA. 25 Dexamethasone at 40 mg/day for 4-6 days is used as a steroid in some chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%